PENGARUH PEMBERIAN DOSIS VITAMIN C TERHADAP SUSUT BOBOT SAPI SELAMA PENGANGKUTAN SAPI DARI PROVINSI LAMPUNG KE PALEMBANG - Restu Agung Triutama; Didik Rudiono; Kusuma Adhianto (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
The operation research were held to elevated effect of vitamin C dosages on cattle body weight lost and determined correlation and regression of temperature, humidity, and length of journey to cattle body weight lost during transportation from Lampung to Palembang.  Research used Completely Randomized Design. The treatments are Control (P0); 1,000 mg vitamin C (P1); 1,500 mg vitamin C (P2); 40 heads respectively.  Research was held on September – November 2015 following cattle transportation from Karang Endah, Central Lampung, Lampung to Tanjung Raja, Indralaya, South Sumatera.  The data were analysed using Analysis of Variance 5% and 1% to know the effect of vitamin C dosage on cattle body weight lost, continued with Least Significance Different 5% and 1%.  Correlation and regression of body weight lost to temperature, humidity, and length of journey were analyzed using correlation and regression analysis.  The results showed vitamin C treatment had highly significant result (P<0,01) on cattle body weight lost during transportation at 9,53% on 1.000 mg vitamin C (P1); and 9,26%  on 1.500 mg vitamin C (P2).  The best results were given by 1.500 mg of vitamin C treatment. The correlation between body weight lost to temperature, humidity, and length of journey were 0,36, 0,054, and 0,17 on P0; 0,26, 0,26, and 0,0003 on P1; 0,24, 0,24, and 0,14 on P2. Keyword : Vitamin C, Transportation, Cattle Body Weight Lost